2001
DOI: 10.1159/000049309
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cannabis Use, Schizotypal Traits, and Cognitive Function in Healthy Subjects

Abstract: This research examined the relationship between cannabis use and schizotypal features. A sample of cannabis users (n = 20) was compared with a matched control group (n = 20). All participants were male students of the University of Hamburg. Subjects completed the Perceptual Aberration Scale and the Schizotypal Personality Questionnaire. A Negative Priming procedure and the Trail Making Test were carried out. A urine sample was obtained from each subject. Cannabis users exceeded controls in schizotypy scores an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 40 publications
4
34
2
1
Order By: Relevance
“…Cannabis has been associated with a worsening of positive symptoms, especially delusions and hallucinations [5,59]. The association between current cannabis use, deficits in attentional inhibition, which has been found to be related to positive symptomatology [60], and higher scores on the Positive Syndrome of the Schizotypal Personality questionnaire, gives further support to this point [25,61]. However, our study found no significant difference in positive symptomatology between the two groups of subjects.…”
Section: Discussionsupporting
confidence: 66%
“…Cannabis has been associated with a worsening of positive symptoms, especially delusions and hallucinations [5,59]. The association between current cannabis use, deficits in attentional inhibition, which has been found to be related to positive symptomatology [60], and higher scores on the Positive Syndrome of the Schizotypal Personality questionnaire, gives further support to this point [25,61]. However, our study found no significant difference in positive symptomatology between the two groups of subjects.…”
Section: Discussionsupporting
confidence: 66%
“…As mentioned before, frontal dysfunction in schizophrenia has been associated with both cognitive deficits and negative symptoms. However, since the frontal cortex is also involved in substance use [47,48] , and since cognitive function alterations have been described in SUDs [31,48,49] , the presence of comorbid SUDs in schizophrenia could be an important confounding factor in the association between cognitive functioning and negative symptoms. With respect to cognitive functions in schizophrenic patients with comorbid SUDs, some authors have found that substance-using patients exhibit better cognitive functioning than nonconsuming patients [50][51][52] , as well as less negative symptoms and better social functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Skosnik et al (2001) found large differences (d ¼ 1.8) on the full SPQ in small groups (N ¼ 15 or less) of current, former, and never users of cannabis. Mass et al (2001) report significant differences between cannabis users (N ¼ 20) and non-users (N ¼ 20) on five of the nine subscales of the SPQ, but three of these were at p < 0.10. Data were not reported in enough detail to compute effect sizes.…”
Section: Introductionmentioning
confidence: 87%